KEBIJAKAN BAHASA DAN PENDIDIKAN: MENYOAL PERDA PROVINSI BENGKULU TENTANG BUDAYA, BAHASA, PENGAJARAN BAHASA, DAN POLITIK BAHASA - Arono Arono (Jurnal Membaca Bahasa dan Sastra Indonesia, 2016)
Law is expected to overcome the various problems associated with the establishment of practices and procedures for the use of language, as well as regulates various matters related to the establishment and procedures for the use of language, including the set of criminal provisions. In fact, of the nine districts and one municipality, only one Rejang Lebong memunyai local regulations in terms of culture, language, language teaching and language politics. Very different from the actual conditions in Bengkulu multicultural society the majority of the other group less thinking about the continuity of language and culture in society. This paper describes the language and education policies on the basis of Rejang Lebong Regional Regulation No. 2 of 2009 on the System of Education in Rejang Lebong realitations not ignore the other conditions in the province of Bengkulu. This paper uses a descriptive qualitative methods literature / documentation, interviews, and observations. Education as theorganizer of the policy is still responding in one setup educators still focus on one language regardless of the language the other so that the effect on the preparation of educators, the school is still very limited apply learning regional languages? are still in local content selection, and the community is still limited on the use of language and cultural traditions without oriented towards sustainability and the preservation of language and culture developed. In addition, the government less responsive and sensitive to the phenomenon of language and culture of minority communities, as well as geography. Grain to issue teaching, politics national language of wider scope than the policy national language, not only covering the curriculum, teaching materials, staff, linguistic, and means, but also to the study of teaching, determination of didactic and methodical appropriate, as well as the development literature. Several attempts to do planning of language in education, namely (1) Language and education work together to establish, maintain and elevate human dignity. (2) The relationship and a close affinity between the development of language and education development takes place in the family, formal education institutions, and communities. (3) There should be an emphasis and review again in terms of both content and use of language teaching methods contained in the curriculum (4) In daily life in the community seems necessary their appetite similarity in the use of language or terms.